Disminución de tiempos improductivos para incrementar la utilización de los equipos de carguío y acarreo en la mejora continua de la productividad en el tajo Chalarina en Minera Shahuindo S.A.C - Apaza Risco, Elmer Danilo (2017)
In the mining company "Shahuindo" the carguío, as well as the transportation of material (mineral and felling) they are unitary operations of importance for the mined one, which must develop in ideal times without generating waste raising the production. Miner Shahuindo, they have faced problems the excess of tails of the equipments of transportation in the fronts of carguío and in the zones of unloads. The carguío and the transportation are some of the most significant operations, for which one seeks to obtain the best results and that are the nearest ones to the planned thing. During the activities of carguío and transportation, the presence of delays, not operative and operative present a problem in the operative KPI'S, the low utilization of our equipments affects the productivity and they do not allow to reach the fulfillment of our monthly production. The present study had as line base the identification of unproductive times and operational losses on the activities of carguío and I transport to generate an action plan with the purpose of standardizing and supporting the constant improvement in each of the activities, this way to have a better productivity and for ende a better performance, with the decrease of unproductive times it will be possible obtain a high utilization and for ende an acceptable productivity on the basis of the cost of the equipment, of carguío and I transport, allowing the fulfillment of the monthly planned production, on the basis of the analysis of the reports of production it was possible to notice that the increase of the operative delays they were the most significant during the operation, this due to certain factors for that they give themselves the such above mentioned delays as area reduced in carguío, area reduced in unload supply of fuel, I change abreast, etc.There was obtained like proved a reduction of 65.6 % in the hours of delay for carguío and of 47.8 % for the hours of delay in I transport respectively. Likewise, the production of mineral was increased in 12.5 % with regard to the mineral to the PAD and of 67.6 % with regard to the stockpile. Another improved indicator is that the monthly production vs presupuestado increased of 47.3 % up to 107 %.